A case of high-grade mucinous tubular and spindle cell carcinoma. Issue 2 (21st February 2020) - Miura, Koujin; Adachi, Yasushi; Shirahase, Toshiaki; Nagashima, Yoji; Suemune, Kazuki; Sakaida, Noriko; Nakano, Yorika; Sakai, Yasuhiro; Shimizu, Shigeki; Ikehara, Susumu
Abstract: Mucinous tubular and spindle cell carcinoma (MTSCC) is a rare renal cell carcinoma that initially presents as low-grade renal cell carcinoma. However, cases of MTSCC with high-grade histology and poor prognosis have been reported. Here, we report a case of MTSCC with high-grade histological features and metastasis. A 77-year-old woman consulted a hospital following frequent and painful micturition. Computed tomography scan revealed a tumor of the left kidney. First, chemotherapy was performed, with no effects. Therefore, nephrectomy was subsequently performed. Histologically, the tumor showed the features of MTSCC with sarcomatoid component. Metastasis of the tumor into the lymph node was also observed. Although adjuvant chemotherapy was performed after nephrectomy, metastasis to the lungs and bone and local recurrence was observed. The patient is still alive 2 years after nephrectomy with metastasis and recurrence of the tumor. High-grade MTSCC shows a relatively poor prognosis, specifically MTSCC with metastasis upon nephrectomy.